2020
DOI: 10.1088/1742-6596/1505/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Effectiveness of Light Emitting Diode (Led) For Inactivation on Staphylococcus aureus Bacteria and Wound Healing in Infectious Wound Mice

Abstract: This study aims to determine the effectiveness of the antimicrobial photodynamic therapy (aPDT) LEDs of 392 nm and 628 nm red LEDs for photoinactivation on Staphylococcus aureus in vitro and the photodynamic effectiveness of therapy for wound healing in mice in vivo. The sample used was Staphylococcus aureus bacterial isolate which was infected on mice incision wounds. The LED exposure was carried out at the energy density of 19.44 J/cm2, respectively. In vitro test samples were divided into three groups, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…20,21 The effect of bacterial photoinactivation on wounds in vivo due to photodynamic therapy in the red LED exposure group was 88%, the blue LED exposure group was 94%, and the red and blue LED combination exposure group was 95%. 20 Blue and red lasers combined with ozone treatment effectively accelerated wound healing of incisions infected with MRSA bacteria. 21 Thus, LED antimicrobial photodynamic therapy is effective for bacterial inactivation and accelerates wound healing in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The effect of bacterial photoinactivation on wounds in vivo due to photodynamic therapy in the red LED exposure group was 88%, the blue LED exposure group was 94%, and the red and blue LED combination exposure group was 95%. 20 Blue and red lasers combined with ozone treatment effectively accelerated wound healing of incisions infected with MRSA bacteria. 21 Thus, LED antimicrobial photodynamic therapy is effective for bacterial inactivation and accelerates wound healing in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The photochemical reactions in PDI are generally of the second type. In vivo studies are found in other journals [20,21]. The effect of bacterial photoinactivation on wounds in vivo due to photodynamic therapy in the red LED exposure group was 88%, the blue LED exposure group was 94%, and the red and blue LED combination exposure group was 95% [20].…”
Section: Open Peer Reviewmentioning
confidence: 99%
“…Malpositioned teeth can cause trauma to the surrounding soft tissues, and teeth with severe fractures may require extraction. Lastly, extractions may be performed for mouth preparation before prosthodontic treatment [4]. Tooth extraction, or simply extraction, is a procedure that involves separating a tooth from the soft tissue that surrounds it and removing a tooth that cannot be retained within its socket using forceps or an elevator.…”
Section: Introductionmentioning
confidence: 99%
“…Wounds can be classified into various degrees, i.e., acute wounds, chronic wounds, and complication wounds, whereas time is an important factor in the wound healing process [4,5]. The process of wound healing in intentional or unintentional tooth extraction differs for each individual.…”
Section: Introductionmentioning
confidence: 99%
“…This non-thermal therapy uses chromophore as a natural photosensitizing agent in photophysical and photochemical processes at various biological scales [21,22]. Also, it is useful in reducing or relieving pain due to inflammation, regulating immunomodulation, as well as improving wound care and tissue regeneration [5,23].…”
Section: Introductionmentioning
confidence: 99%